Evaluation of lactobacillus paracasei LP11 and lactobacillus rhamnosus 64 potential as candidates for use as probiotics in functional foods - de Matos, Fernando Eustáquio (2020)
Desirable characteristics for probiotic microorganisms were evaluated in Lactobacillus rhamnosus 64 and Lactobacillus paracasei LP11. Both strains were tested for resistance to lysozyme and simulated gastrointestinal fluids, determination of cell wall hydrophobicity, evaluation of antibiotic susceptibility, antagonist activity against pathogens and the ability to use prebiotics. The safety determination was performed by an in vivo test, where the occurrence of bacterial translocation to liver was evaluated after daily oral administration of the strains for 10 days to mice. All results were promising, with the exception of resistance to simulated gastrointestinal fluids, that was unsatisfactory, with a decrease in viable cell concentrations of up to 5.08 log CFU/mL. The hydrophobicity profile of the strains ranged between 8.47 and 19.19%. Both showed satisfactiry resistance to lysozyme, with survival rates above 80%, strains were able to antagonize Escherichia coli V517, Salmonella enteritidis OMS-Ca, Staphylococcus aureus 76 and Listeria monocytogenes ATCC 15313, and displayed satisfactory use of lactulose, inulin and P95 raftilose as prebiotics. No bacterial translocation was observed after the administration of the strains to mice. The results obtained herein justify the use of L. rhamnosus 64 and L. paracasei LP11 in new investigations for the future application of these microorganisms as probiotics.